An extraordinary experience - Khan , S (INDIA , Good word books, 2010)
"An Extraordinary Experience" by Saniyasnain Khan is a children's book that introduces young readers to the profound journey of Prophet Yunus (Jonah). Through simple language and engaging illustrations, the story narrates how Prophet Yunus was swallowed by a giant fish and spent three days and nights in its belly. During this time, he reflected on his actions and sought forgiveness, highlighting themes of repentance, patience, and the mercy of Allah. The book aims to impart moral lessons to children, emphasizing the importance of self-reflection and seeking forgiveness.